Resilient coastal city regions : planning for climate change in the United States and Australia - Blakely, Edward J. (Edward James), 1938-; Carbonell, Armando, 1951- (Lincoln Institute of Land Policy, 2012)
"The importance of dealing with potentially severe climate impacts is becoming increasingly clear. In recent years, we have seen a number of extreme temperature and precipitation events, with climate records set in countries around the globe, but notably in the United States and Australia. The Lincoln Institute initially became involved in the issue of climate change through our work with planning directors in the 30 largest cities of the United States. Beginning in 2006 these city planners started raising the issue of how to respond to their mayors' questions about global warming. Many of the mayors were already signing the U.S. Conference of Mayors Climate Protection Agreement, launched by Seattle Mayor Greg Nickels in 2005 as the Kyoto Protocol was going into effect. Building on a number of Institute-sponsored working papers, Policy Focus Reports, and research seminars over the past five years, this book reports on responses to climate change in nine coastal cities and metropolitan regions in the United States and Australia. The two countries, both large, sprawling, and showing a predilection for coastal development, have much in common when it comes to climate change. First, they are among the highest greenhouse gas (GHG) emitters per capita in the developed world, with Australia usually heading the list and the United States close behind. Second, both countries are exposed to significant climate-related risk relative to sea level rise and storm surge, drought and water shortage, floods, wildfires, and heat waves. The city regions documented here represent some of the most critical conditions faced in the two countries. This book deals with both mitigation (the reduction of GHG emissions) and adaptation (managing the risk of climate impacts that cannot be avoided) as the terms are generally used in this field. At least from the vantage point of the United States, it appears that the pendulum has swung from an initial emphasis on mitigation, as reflected in the mayors' initiatives in response to the Kyoto Protocol, to one focusing on adaptation, as cities begin to prepare for the onslaught of climate-related impacts. The nine cases show a range of adaptation responses. However, as explored in the concluding chapter, to avoid catastrophic results, it remains necessary to significantly reduce GHG emissions. While there are encouraging developments at the national level in Australia, recent analysis suggests that the time for action is critically short. The pivotal environmental issue of our time has largely left the world stage as governments across the globe struggle for economic stability in the wake of the financial crisis of 2008. In spite of mixed prospects for action at the international and national levels, state and local governments have shown a greater ability to respond to climate change. Resilience and adaptation are coming to the fore in public discussions, with increasing attention given to the impacts of changes in climate on human welfare and the integrity of ecosystems. In bringing forth this volume, the aim was to document approaches that will be useful not just in the United States and Australia but more broadly in coastal regions throughout the world. We are humbly aware that this is only an initial response to a challenge with a magnitude of potential impacts never before experienced in human history, a challenge that will test our ability to work together at every scale."--Publisher's website